Using cementochronology to assess the seasonality of catastrophic events in medieval mass graves (Kutná Hora-Sedlec, Czechia, 14th century): Preliminary results - Zazvonilová, Eliška; Brzobohatá, Hana; Frolík, Jan; Velemínský, Petr; Brůžek, Jaroslav (PloS one, 2023)
While season-of-death estimation using cementochronology is routine in archaeozoology, its use is much less frequent in bioarchaeology. Based on the character of the outermost increment (bright or dark), two seasons (spring/summer, autumn/winter) can be distinguished. Although many studies mention its potential and possible use in forensic anthropology or bioarchaeology, few exist with estimation results. This study aimed to apply cementochronology-a histological method based on counting and assessing regular circa-annual acellular cementum increments-to 42 individuals from medieval mass graves from Kutná Hora-Sedlec (Czechia, 14th century) to estimate the season-of-death. The mass graves belong to two stratigraphically distinct groups; written and archaeological sources relate them to two catastrophic events (the famine of 1318 and the plague epidemic of 1348-1350). Using cementochronology, we distinguished two distinct seasons corresponding to the two groups of graves, with individuals from the first group dying predominantly in spring/summer, while those from the second group died in autumn/winter. Taking into account the typical seasonal dynamics of epidemics, the results would be more in line with written sources. However, during the evaluation, we faced difficulties identifying the outermost increment and detecting the dark (thinner) increment; we recommend including only young and middle-aged adults in future studies, due to the difficulty of evaluation, and to consider the readability of the tissue (often affected by diagenesis). In conclusion, cementochronology has potential in the context of estimating the season-of-death, but the technical possibilities for enhancing the outermost increment need to be addressed, and the amount of data analysed expanded.
Keywords: Cognition; dospělí; Česká republika; archeologie; kognice; Age Determination by Teeth; lidé středního věku; Archaeology; lidé; Seasons; určení zubního věku; soudní antropologie; Czech Republic; Middle Aged; roční období; Adult; Forensic Anthropology; Humans